2001
DOI: 10.1098/rstb.2000.0753
|View full text |Cite
|
Sign up to set email alerts
|

Transcription, β–like DNA polymerases and hypermutation

Abstract: This paper discusses two aspects of immunoglobulin (Ig) gene hypermutation. In the ¢rst approach, a transcription termination signal is introduced in an Ig light chain transgene acting as a mutation substrate, and transgenic lines are generated with control and mutant transgenes integrated in tandem. Analysis of transcription levels and mutation frequencies between mutant and control transgenes clearly dissociates transcription elongation and mutation, and therefore argues against models whereby speci¢c pausin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…This activity is based on the preferential expression of pol μ in secondary lymphoid tissues as well as its low fidelity during the replication of undamaged DNA [132]. Additionally, the ability of pol μ to bypass several DNA lesions through a deletion mechanism provides circumstantial evidence for its role as a mutase during somatic hypermutation [133]. A perspective on the role of certain X-family DNA polymerases in regulating nucleic acid integrity is provided in a recent review by Ramadan et al [134].…”
Section: Structural Insights Into the Mechanism Of Tdtmentioning
confidence: 99%
“…This activity is based on the preferential expression of pol μ in secondary lymphoid tissues as well as its low fidelity during the replication of undamaged DNA [132]. Additionally, the ability of pol μ to bypass several DNA lesions through a deletion mechanism provides circumstantial evidence for its role as a mutase during somatic hypermutation [133]. A perspective on the role of certain X-family DNA polymerases in regulating nucleic acid integrity is provided in a recent review by Ramadan et al [134].…”
Section: Structural Insights Into the Mechanism Of Tdtmentioning
confidence: 99%
“…Numerous human and murine Polµ splice variants have been described representing approximately 90% of Polµ mRNA species, in which splicing affected exons 5 to 11, encoding the active site of the polymerase. In most cases, these splicing events induced a premature stop codon and truncated proteins [23], [27], which could function as regulators of the activity of this enzyme [36]. Similarly, the splice variant detected in this study lacks one part of its active site and will consequently likely be nonfunctional.…”
Section: Discussionmentioning
confidence: 74%
“…Figure 2B also shows that the expression of Polµ in the spleen decreases with age. Some authors have suggested that due to its mutagenic potential, its preferential expression in secondary lymphoid tissues and its expression in the nucleus of centroblasts from human tonsils, Polµ could play a role in somatic hypermutation of Ig genes [24][27]. However, an analysis of Polµ-deficient mice did not support this hypothesis [36], [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both human Pol ␤ and human Pol show deoxyribose phosphate lyase activity, indicative of their ability to process intermediates in the DNA glycosylase-initiated repair of damaged bases (35,36). A function for Pol in somatic hypermutation has been proposed based upon its low fidelity of DNA synthesis in vitro and its cell type-specific expression pattern in mammals (5,37). Moreover, a more general role of Pol in non-homologous end joining of double-stranded DNA breaks has also been proposed (38).…”
Section: Classification Of Dna Polymerases and Occurrence Across Eukamentioning
confidence: 99%